Study protocol: realist evaluation of effectiveness and sustainability of a community health workers programme in improving maternal and child health in Nigeria. (December 2015) - Mirzoev, Tolib; Etiaba, Enyi; Ebenso, Bassey; Uzochukwu, Benjamin; Manzano, Ana; Onwujekwe, Obinna; Huss, Reinhard; Ezumah, Nkoli; Hicks, Joseph; Newell, James; Ensor, Timothy
Abstract Background Achievement of improved maternal and child health (MCH) outcomes continues to be an issue of international priority, particularly for sub-Saharan African countries such as Nigeria. Evidence suggests that the use of Community Health Workers (CHWs) can be effective in broadening access to, and coverage of, health services and improving MCH outcomes in such countries. Methods/design In this paper, we report the methodology for a 5-year study which aims to evaluate the context, processes, outcomes and longer-term sustainability of a Nigerian CHW scheme. Evaluation of complex interventions requires a comprehensive understanding of intervention context, mechanisms and outcomes. The multidisciplinary and mixed-method realist approach will facilitate such evaluation. A favourable policy environment within which the study is conducted will ensure the successful uptake of results into policy and practice. A realist evaluation provides an overall methodological framework for this multidisciplinary and mixed methods research, which will be undertaken in Anambra state. The study will draw upon health economics, social sciences and statistics. The study comprises three steps: (1) initial theory development; (2) theory validation and (3) theory refinement and development of lessons learned. Specific methods for data collection will include in-depth interviews and focus group discussions with purposefully identified key stakeholders (managers, service providers and service users), document reviews, analyses of quantitative data from the CHW programme and health information system, and a small-scale survey. The impact of the programme on key output and outcome indicators will be assessed through an interrupted time-series analysis (ITS) of monthly quantitative data from health information system and programme reports. Ethics approvals for this study were obtained from the University of Leeds and the University of Nigeria. Discussion This study will provide a timely and important contribution to health systems strengthening specifically within Anambra state in southeast Nigeria but also more widely across Nigeria. This paper should be of interest to researchers who are interested in adapting and applying robust methodologies for assessing complex health system interventions. The paper will also be useful to policymakers and practitioners who are interested in commissioning and engaging in such complex evaluations to inform policies and practices.